The CD105:CD106 microparticle ratio is CD106 dominant in polycystic ovary syndrome compared to type 2 diabetes and healthy subjects - Al-Qaissi, Ahmed; Alqarni, Saeed; Javed, Zeeshan; Atkin, Stephen L.; Sathyapalan, Thozhukat; Vince, Rebecca V.; Madden, Leigh A. (Endocrine, 2019)
Background A retrospective analysis was carried out from patients and controls during the past 5 years from a series of studies investigating endothelial microparticles (MP). Methods In total, 319 samples from 207 individuals were included in this analysis, from patients with type 2 diabetes (T2D, n = 105), women with polycystic ovary syndrome (PCOS, n = 145) and healthy volunteers ( n = 69). All data were generated via the same flow cytometry protocol with the same antibody clones. Endothelial markers CD105 (Endoglin) and CD106 (Vascular cell adhesion molecule-1) were used to enumerate MP in venous blood. Results The ratio of CD105MP:CD106MP was significantly different between groups ( F = 63.43, p < 0.0001). Women with PCOS were found to have a median CD105MP:CD106MP ratio of 0.40 (IQR 0.24–0.57), suggesting approximately two CD106MP were found per CD105MP. The T2D group showed a median ratio of 2.32 (1.51–3.69) whereas in healthy volunteers the ratio was 2.21 (1.63–3.55). Serum intercellular adhesion molecule-1 was also shown to be significantly increased in PCOS when compared with control or T2D groups ( F = 14.5, p < 0.001). Conclusion These data suggest that women with PCOS have an altered endothelial MP release in favour of CD106. Thus a potential activated endothelial state exists in women with PCOS with a shift towards a predominantly CD106MP profile.